(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This study explores the role and future prospects of high-entropy alloys (HEAs) in the mining and metallurgical industries. Due to their exceptional microstructural stability, high mechanical strength, wear resistance and heat tolerance, HEAs represent a promising alternative to conventional metallic materials used in drilling tools, cutting elements and components operating under extreme loading conditions. In this research, an AlCoCrNi-based HEA was synthesized, its phase composition was analyzed, and the effects of heat treatment on microstructural evolution and mechanical performance were investigated. Experimental field trials demonstrated that HEA-based drilling elements exhibited enhanced durability and operational stability compared with conventional alloys. The findings indicate that HEAs offer significant advantages in extending equipment lifetime, improving reliability and reducing maintenance costs within the mining industry. The obtained results provide scientific and practical foundations for further optimization and industrial implementation of HEA-based materials.